Low-cost shared mobility alternatives in rural areas: A case study of ride-sharing benches in the German-speaking community of Belgium. Issue 4 (December 2022) - Madani, Negarsadat; Creemers, Lieve; Moeinaddini, Mehdi; Saadi, Ismaïl; Cools, Mario
Highlights: We introduce a low-cost shared mobility solution for rural areas. An online survey was conducted to assess the knowledge of the concept. The users consider using the benches in combination with the scheduled bus service. This service can be a low-cost and practical shared mobility solution. The locations of the benches can be integrated into an application. Abstract: This paper focuses on a low-cost shared mobility solution in the German-speaking Community of Belgium (Ostbelgien). Like many other rural areas, Ostbelgien is car-oriented and has low public transport coverage. The main objective of this paper is to introduce the concept of ride-sharing benches in Ostbelgien. In addition, an online survey was conducted to assess the knowledge of the concept and its potential use according to socio-economic, socio-cognitive, and geographic characteristics. The survey demonstrated that there is a high potential for using it in the future. Socio-economic and socio-cognitive factors determine the potential use of ride-sharing benches, whereas geographical factors predominantly influence knowledge of the concept. The users consider using the benches in combination with the scheduled bus service. This service can be a low-cost and practical shared mobility solution, especially for rural areas with low public transportation coverage. The locations of the benches can be integrated into an application to stimulate the use of the ride-sharing benches.